PENGARUH SHOLAT DHUHA BERJAMAAH TERHADAP KESIAPAN MENTAL PESERTA DIDIK DALAM KEGIATAN BELAJAR MENGAJAR DI MTS SILA KABUPATEN BIMA - Ainun Khatimah; Mustamin; Abdul Wahab; Akhmad Syahid; Andi Hasriani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the implementation of congregational Dhuha prayer, students’ mental readiness in teaching and learning activities, and the effect of congregational Dhuha prayer on students’ mental readiness at MTs Sila, Bima Regency. This study employed a quantitative approach with a correlational research design. The research sample consisted of 63 students. Data were collected through questionnaires and documentation. The data were analyzed using descriptive analysis and multiple linear regression with the assistance of SPSS. The results showed that the implementation of congregational Dhuha prayer, which includes discipline in performing Dhuha prayer, concentration and devotion during Dhuha prayer, as well as togetherness and socio-religious values, was categorized as moderate. Students’ mental readiness in teaching and learning activities was also categorized as moderate. The partial test results showed that discipline in performing Dhuha prayer had a positive and significant effect on students’ mental readiness, with a t-value of 4.448 and a significance value of 0.000; concentration and devotion during Dhuha prayer had a positive and significant effect, with a t-value of 5.513 and a significance value of 0.000; and togetherness and socio-religious values had a positive and significant effect, with a t-value of 2.253 and a significance value of 0.028. Simultaneously, the three variables had a significant effect on students’ mental readiness, with an F-value of 121.184 and a significance value of 0.000. The R Square value of 0.860 indicates that the implementation of congregational Dhuha prayer contributed 86% to students’ mental readiness, while the remaining 14% was influenced by other factors outside the study. The variable with the greatest contribution was concentration and devotion during Dhuha prayer.